2017
DOI: 10.1021/acs.energyfuels.7b01526
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergy Generation from Municipal Solid Waste and Glycerin Waste: Population Dynamics

Abstract: This paper studies the microbial community, effluent characteristics, and bioenergy generation (hydrogen and methane production) in a two-phase dry-thermophilic (55 °C) anaerobic codigestion process treating actual municipal solid waste (20% solid content) and biodiesel waste (glycerin waste, 1% v/v). Four different hydraulic retention times (from 11.5 to 4.5 d) and four organic loading rates (from 8.2 to 21.1 g VS/L/d) were studied to identify optimal conditions (maximum values of biogas and microbial activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…A high solubilization (increase in SCOD and VFA and decrease in VS) was detected. The butyrate acid concentration was higher than acetic acid concentration and it was in line to other researches of hydrogen production from similar wastes (Cadiz-Spain urban wastes) (Romero Aguilar et al 2013;Zahedi et al 2013b;Angeriz-Campoy et al 2017;Zahedi et al 2017a). The ratio of butyrate:acetate (g butyrate/g acetate) was 2.5 and it according to the ratios reported by these previous studies.…”
Section: Hydrogenic Phase Performancesupporting
confidence: 91%
See 1 more Smart Citation
“…A high solubilization (increase in SCOD and VFA and decrease in VS) was detected. The butyrate acid concentration was higher than acetic acid concentration and it was in line to other researches of hydrogen production from similar wastes (Cadiz-Spain urban wastes) (Romero Aguilar et al 2013;Zahedi et al 2013b;Angeriz-Campoy et al 2017;Zahedi et al 2017a). The ratio of butyrate:acetate (g butyrate/g acetate) was 2.5 and it according to the ratios reported by these previous studies.…”
Section: Hydrogenic Phase Performancesupporting
confidence: 91%
“…The cellular concentration and percentages of Bacteria and Archaea were quantified by epifluorescence method (FISH) according to the method of Zahedi et al (Zahedi et al 2013c;Zahedi et al 2017a). The main steps of FISH of whole cells using 16S rRNAtargeted oligonucleotide probes are cell fixation, permeabilisation and hybridisation with the desired probe(s).…”
Section: Microbiological Analysis and Biochemical Activitymentioning
confidence: 99%
“…Several studies have been carried out using a MSW-fueled downdraft gasifier. Starting from the feasibility study of MSW as a fuel for gasification, , energy analysis resulting from the gasification process, analysis of the thermodynamic equilibrium model of MSW gasification, and a techno-economy analysis of MSW gasification for electricity generation were studied. Based on these studies it can be concluded that MSW has the potential to be used as a gasification feedstock.…”
Section: Introductionmentioning
confidence: 99%
“…The MSWI fly ash which contains a large number of heavy metal substances is a subsidiary product of waste incineration power generation technology. Failing to dispose the MSWI fly ash properly, secondary pollution will cause serious environment safety problems 1924 .…”
Section: Introductionmentioning
confidence: 99%